The intergenerational effect of tuition-free lower-secondary education on children's nutritional outcomes in Africa - Alfredo Martin; Aleta Sprague; Amy Raub; Bijetri Bose; Pragya Bhuwania; Rachel Kidman; Arijit Nandi; Jere Behrman; Jody Heymann (Taylor & Francis Group, 2024)
ABSTRACTOne in five child deaths under age 5 are a result of severe wasting. Malnutrition at early ages is linked to lifelong consequences, such as reduced cognitive skills, reduced earnings in adulthood and chronic health conditions. Countries worldwide have committed to addressing child undernutrition, and ending hunger is foundational to the Millennium Development Goals. In this paper, we study the intergenerational effect of providing free tuition in secondary school on future children's nutrition. We combined a novel longitudinal dataset that captures educational policies for 40 African countries from 1990 to 2019 with the Demographic and Health Survey (DHS). We identified three countries that introduced free secondary education several years after implementing free primary education. Exploiting this variation in timing we estimate the additional impact of providing free secondary education over free primary education. Using a difference-in-difference approach, we find that introducing free secondary education significantly reduced wasting. Cohorts exposed to free secondary had an 18% relative decrease in wasting. The impact on cohorts exposed only to free primary was smaller and not statistically significant. Expanding free secondary education has long-term, intergenerational benefits and is an effective path to reducing malnutrition. Results are robust to different specifications.